Identifikasi Keberadaan Air Tanah Menggunakan Metode Geolistrik di Desa Wolonmaget Nusa Tenggara Timur - wahyuni, yayu sri; Priambodo, Sebastianus (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2024)
This research aims to present a comprehensive overview of the distribution of rock layers and inform the presence of rock layers that function as aquifers (water-carrying layers) in the Wolonmaget Village area, Wolonmaget Sub-district, Alok Barat District, Sikka Regency, East Nusa Tenggara, using the method of geolectric. This research type is field research (in situ test) and uses quantitative data by directly collecting data or test samples in the field at 3 (three) observation points: GL1, GL2, and GL3. This study result show that the area being investigated through geoelectric estimation has provided a description of the rock layer conditions, both vertically and laterally. The hydrological conditions in the study area are included in a local productive aquifer system with rocks that are expected to act as aquifers, specifically Tuff Sand. Based on the geoelectric investigation, the aquifer layers identified are: GL.01 at a depth of 73.66-200.000 meters with a thickness of 138.36 meters; GL.02 at a depth of 61.64-200.000 meters with a thickness of 138.36 meters; GL.03 at a depth of 61.22-2000 meters with a thickness of 138.78 meters.